Arctic and boreal paleofire records reveal drivers of fire activity and departures from Holocene variability. Issue 9 (9th June 2020) - Hoecker, Tyler J.; Higuera, Philip E.; Kelly, Ryan; Hu, Feng Sheng
Abstract: Boreal forest and tundra biomes are key components of the Earth system because the mobilization of large carbon stocks and changes in energy balance could act as positive feedbacks to ongoing climate change. In Alaska, wildfire is a primary driver of ecosystem structure and function, and a key mechanism coupling high‐latitude ecosystems to global climate. Paleoecological records reveal sensitivity of fire regimes to climatic and vegetation change over centennial–millennial time scales, highlighting increased burning concurrent with warming or elevated landscape flammability. To quantify spatiotemporal patterns in fire‐regime variability, we synthesized 27 published sediment‐charcoal records from four Alaskan ecoregions, and compared patterns to paleoclimate and paleovegetation records. Biomass burning and fire frequency increased significantly in boreal forest ecoregions with the expansion of black spruce, ca. 6, 000–4, 000 years before present (yr BP). Biomass burning also increased during warm periods, particularly in the Yukon Flats ecoregion from ca. 1, 000 to 500 yr BP. Increases in biomass burning concurrent with constant fire return intervals suggest increases in average fire severity (i.e., more biomass burning per fire) during warm periods. Results also indicate increases in biomass burning over the last century across much of Alaska that exceed Holocene maxima, providing important context for ongoing change. Our analysis documents the sensitivity of fire activity to broad‐scale environmental change, including climate warming and biome‐scale shifts in vegetation. The lack of widespread, prolonged fire synchrony suggests regional heterogeneity limited simultaneous fire‐regime change across our study areas during the Holocene. This finding implies broad‐scale resilience of the boreal forest to extensive fire activity, but does not preclude novel responses to 21st‐century changes. If projected increases in fire activity over the 21st century are realized, they would be unprecedented in the context of the last 8, 000 yr or more.